Diskrepansi Norma Hukum Agraria dalam Penanganan Bencana: Kajian Yuridis Tanah Musnah Akibat Banjir Bandang di Sumatera - M. Mustofah Bisri (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
The flash flood disaster that struck Aceh, North Sumatra, and West Sumatra in November-December 2025 resulted in 1,053 fatalities, 572,000 displaced persons, over 100,000 damaged housing units, and 90,601 hectares of affected rice fields. The existing agrarian legal framework has failed to provide adequate legal protection. Articles 27, 34, and 40 of Law Number 5 of 1960 (BAL) stipulate that destroyed land results in the extinguishment of land rights, reinforced by Article 1 paragraph 12 of Government Regulation Number 18 of 2021. Meanwhile, Article 1 paragraph 8 of Ministerial Regulation 17/2016 and Article 1 paragraph 7 of Ministerial Regulation 12/2021 stipulate that emerging land is directly controlled by the state. This normative ambiguity creates legal uncertainty. This study aims to analyze the discrepancy of agrarian legal norms in handling destroyed land and formulate an ideal model reconstruction adaptive to disaster management. This normative legal research employs statutory, conceptual, and comparative law approaches, using primary legal materials including the BAL, Law Number 24 of 2007, Presidential Regulation Number 86 of 2018, Presidential Regulation Number 62 of 2023, and relevant ministerial regulations, analyzed qualitatively and comparatively. The findings reveal discrepancies across three dimensions: normative ambiguity in land legal status, implementation obstacles in re-legalization, land redistribution, and religious assistance fund policies due to complex cross-sector coordination and the absence of standard operating procedures for emergency situations, and limited institutional capacity. This study formulates an ideal model reconstruction through legal status reformulation using the “disaster-affected land” concept, procedural simplification through “emergency land procedures”, and corporate responsibility integration based on the polluter pays principle.